The first belemnite of boreal ancestry from the Early Cretaceous (Valanginian) of the western Tethys - Mutterlose, Jörg (Prof. Dr.); Picollier, Marie‑Claire; Dzyuba, Oksana (Dr. rer. nat.) (2022)
The first occurrence of the belemnite species \(Liobelus acrei\) (formerly \(Acroteuthis acrei\)) is reported from the Lower Cretaceous (Valanginian) of the Vocontian Basin (VB; south-east France). This first record of the genus \(\it Liobelus\) (Family Cylindroteuthididae), which is commonly attributed to the latest Jurassic and Early Cretaceous of the Boreal Realm, revises the spatial distribution pattern of boreal belemnites significantly. The Valanginian belemnite assemblages of the VB are dominated by genera of Tethyan ancestry, including both Duvaliidae (\(Berriasibelus, Castellanibelus, Duvalia, Pseudobelus\)) and Belemnopseidae (\(Adiakritobelus, Hibolithes, Mirabelobelus, Vaunagites\)). These two groups of Tethyan taxa comprise more than 99.9% of the belemnite-rich assemblages of the Valanginian of the VB. The occurrence of a boreal specimen documents an isolated immigration of belemnites from the north in the early Valanginian. At the same time most Tethyan belemnite taxa are absent from the Boreal Realm, only \(\it Duvalia\), \(\it Pseudobelus\) and \(\it Hibolithes\) have been described from North-East Greenland, and \(\it Hibolithes\) from Svalbard. Based on these diverging biogeographical patterns of the Tethyan belemnite genera we establish two taxonomically different belemnite faunas: Tethyan Fauna 1 (\(Duvalia, Pseudobelus, Hibolithes\)), which has a near global, Tethyan-wide and even boreal distribution, and Tethyan Fauna 2 (\(Adiakritobelus, Berriasibelus, Castellanibelus, Mirabelobelus, Vaunagites\)), which is less widely distributed and is restricted to southern Europe. These different spatial distribution patterns shed light on the ecology, migration patterns and evolution of Early Cretaceous belemnites.